(untitled) (Journal of the College of Basic Education, 2022)
The current research aimed to identify the extent to which physics teachers are aware of high-ranking thinking skills in Dhi Qar Governorate / Shatrah District, The research sample consisted of (100) physics teachers who study in the middle school day for boys, the scientific branch of the Directorate of Education of Dhi Qar Governorate / Shatrah District, The researchers used a tool to measure the high-ranking thinking skills of the members of the research sample, which was represented by the questionnaire and presented to a group of arbitrators, and its psychometric properties were extracted, The researchers used a set of statistical methods, including the one-sample t-test, the Pearson correlation coefficient, and the Alpha Kron-Bach equation, The results showed the availability of high-ranking thinking skills among physics teachers, and the research came out with a set of recommendations and suggestions